Perancangan Absensi Online Karyawan PT Sinar Surya Komindo dengan Wajah dan Deteksi Lokasi Berbasis Web - Bintang Fahrezi; Suhanda Saputra (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2026)
Employee attendance is one of the key factors in supporting company performance. PT Sinar Surya Komindo currently uses a fingerprint-based attendance system, which has several drawbacks, such as dependency on the physical condition of fingers, electricity supply, limited real-time attendance monitoring, and inefficient data reprocessing. Based on these issues, this research aims to design a web-based online attendance application using face capture and location detection technologies as a solution to enhance the efficiency of the attendance system. The theoretical foundation includes concepts of information systems, employee attendance, location-based services, and software development methods. The research methodology applied is the Waterfall model, consisting of requirements analysis, system design, implementation, testing, and maintenance phases. Data was collected through observations, interviews with the HR department, and literature study. The results indicate that the designed attendance application can more accurately record employee attendance, improve efficiency through real-time monitoring and data reprocessing, and simplify attendance management using face capture and location detection technology. Thus, this application can improve the efficiency and effectiveness of employee attendance management at PT Sinar Surya Komindo